2020
DOI: 10.3390/pr8091082
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Scale Approach to Modeling the Interfacial Reaction Kinetics of Lipases with Emphasis on Enzyme Adsorption at Water-Oil Interfaces

Abstract: The enzymatic hydrolysis of triglycerides with lipases (EC 3.1.1.3.) involves substrates from both water and oil phases, with the enzyme molecules adsorbed at the water-oil (w/o) interface. The reaction rate depends on lipase concentration at the interface and the available interfacial area in the emulsion. In emulsions with large drops, the reaction rate is limited by the surface area. This effect must be taken into account while modelling the reaction. However, determination of the interfacial saturation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that proteins can adsorb to oil–water interfaces due to the presence of both hydrophobic and hydrophilic domains 27–29 . We hypothesized that in our ddRT‐LAMP assay, the unexpected slowdown in assay time in smaller droplets resulted from surface adsorption at the oil‐water interface, and specifically from adsorption of the Bst 2.0 polymerase in the RT‐LAMP reaction.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have demonstrated that proteins can adsorb to oil–water interfaces due to the presence of both hydrophobic and hydrophilic domains 27–29 . We hypothesized that in our ddRT‐LAMP assay, the unexpected slowdown in assay time in smaller droplets resulted from surface adsorption at the oil‐water interface, and specifically from adsorption of the Bst 2.0 polymerase in the RT‐LAMP reaction.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have demonstrated that proteins can adsorb to oil-water interfaces due to the presence of both hydrophobic and hydrophilic domains. [27][28][29] We hypothesized that in our ddRT-LAMP assay, the unexpected slowdown in assay time in smaller droplets resulted from surface adsorption at the oil-water interface, and specifically from adsorption of the Bst 2.0 polymerase in the RT-LAMP reaction. We hypothesized this protein adsorption at the oil-water interfaces in smaller droplets would lead to a reduction in the concentration of free Bst 2.0 available for the ddRT-LAMP reaction, resulting in longer assay times in smaller droplets.…”
Section: Protein Adsorption At the Oil-water Interface Delays Sars-co...mentioning
confidence: 99%
“…TAG levels and lipid droplet surface area are increased at 37°C in Col‐0 but not in pdat1 , such that the higher TAG hydrolysis rate in Col‐0 may initially simply reflect the larger lipid droplet surface area at 37°C without changing the lipase protein levels. The rate of TAG hydrolysis depends on the amount of active enzymes in the lipid‐water‐interphase and the surface area of the lipid droplet (Marangoni, 1994; Rusli et al., 2020). Alternatively, TAG degradation rates could be regulated in response to cellular demand for energy or C 2 carbon skeletons.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, MRGO-IDA-Cu-CotA laccase forms an additional layer at the interface of oil and solution, extending the interface by acting as an amphiphilic surfactant. As a result, the addition of MRGO-IDA-Cu-CotA laccase significantly lowers capillary forces while increasing capillary number [37]. Moreover, in the case of MRGO-IDA-Cu-CotA laccase (0.3 %wt), the interfacial tension values were reduced more than MRGO-IDA-Cu-CotA laccase (0.1 %wt) and MRGO-IDA-Cu-CotA laccase (0.2 %wt), as shown in Table 2.…”
Section: Ift Measurementsmentioning
confidence: 99%